Afet ve Krizlerde Sosyal Hizmet - Bilican Gökkaya, Veda; Öngören, Bülent; Temiz Sarıkaya, Sibel; Özler Ervüz, Feyza; Ervüz, Cezmi; Gülmez, Abdullah; Dilmen, Enes; Dilmen, Fatma; Türk, Ahmet; Bilican Gökkaya, Veda; Kelebek Küçükarslan, Görkem; Balcı, Sinan; et al. (Academician Publishing Book DOI Portal, 2023)
-